2017
DOI: 10.1111/disa.12241
|View full text |Cite
|
Sign up to set email alerts
|

Individual relocation decisions after tornadoes: a multi‐level analysis

Abstract: This study examines how multi-level factors affected individuals' relocation decisions after EF4 and EF5 (Enhanced Fujita Tornado Intensity Scale) tornadoes struck the United States in 2013. A telephone survey was conducted with 536 respondents, including oversampled older adults, one year after these two disaster events. Respondents' addresses were used to associate individual information with block group-level variables recorded by the American Community Survey. Logistic regression revealed that residential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Maghfiroh & Hanaoka, 2019; Maldonado et al, 2013). Indeed, the resilience of individual livelihoods and other socioeconomic impacts often influence relocation decisions (Cong et al, 2018). Additionally, social capital, including community network and place identities, are also integral to relocation decisions (Chamlee‐Wright & Storr, 2009; Cong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Maghfiroh & Hanaoka, 2019; Maldonado et al, 2013). Indeed, the resilience of individual livelihoods and other socioeconomic impacts often influence relocation decisions (Cong et al, 2018). Additionally, social capital, including community network and place identities, are also integral to relocation decisions (Chamlee‐Wright & Storr, 2009; Cong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some vulnerability factors could be resilience factors under certain contexts. For example, although a higher percentage of older adults has traditionally been regarded as an indicator of community vulnerabilities (ATSDR, 2018; Cutter et al, 2003), a study showed that older adults were less likely to relocate after disasters in communities with higher percentages of older adults, which implies that community vulnerabilities are contextual and could also be resilience factors (Cong et al, 2018). Other researchers have proposed community vulnerability indicators specifically designed for older adults, which deserves extensive in-depth studies in the future (Chau et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to perceived and objective risk, studies have found that individual adaptation attitudes and behavior can be positively influenced by disaster experience (Cong et al 2018;Osberghaus 2017). Personal experience with disaster can have a powerful impact on "the willingness to protect oneself from that risk" (Martin et al 2009, p. 491).…”
Section: Conceptual Framework Of Individual-level Support For Hazard ...mentioning
confidence: 99%